(3aJM GdeLjO hcaGjI GdeQjOs - (3YHO GdSdGe Hf EHQGgje Hf EHQGgje GdeGdcj GddbGfj,J (B1078 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa GdJhMjO hgOi deYQaJg ef CSYOg abGd UhGHkG hjS dg ef eWGdYI COdI eG jcajg YfO JhLg GdSDGd Ydjg LhGHkG s
(3BNQgG (B:s
(3bGd LYaQ GdUGOb QVi Gddg Yfg (B: (3gd LRGA ef CMSfJ Ydjg ai GdCRd EdG MaX GdEfSGf ai GdCOH hMjK CJjfG HYhf Gddg Ydi eG bUOfG hHdZfG ef GdaJM eG ChQOfG hCaVd GdUdGI hCTQa GdJSdje Ydi SjOfG eMeO GdeNUhU HeRjO GdcQje hYdi Bdg hGUMGHg CLeYjf Edi jhes
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG eWGdYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B355s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B172s
Keywords: (3GdJhMjO hGdedd hGdfMds